Tegangan Geser Kritis di Hulu Bendung, Studi Kasus Pada Bendung Sekka-Sekka, Kabupaten Polewali Mandar - Rohani, Imam; Ridhayani, Irma; Suniarta, Delmi (Universitas Batanghari Jambi, 2025)
The upstream section of the Sekka-Sekka Weir plays an important role in the irrigation water distribution system but is highly vulnerable to sedimentation due to severe bed erosion. Excessive sedimentation can reduce the weir’s storage capacity and hinder irrigation efficiency. Therefore, this study aims to analyze flow shear stress and critical shear stress to understand the potential for sediment transport in the area. A quantitative approach was used by simulating flow conditions with HEC-RAS to obtain flow characteristics and river cross-sections under three discharge conditions: maximum, minimum, and average. Sediment samples were collected from the field and analyzed in the laboratory using sieve analysis and specific gravity tests, while critical shear stress was determined using the Shields diagram. The results showed that under maximum discharge, flow shear stress (6.169–6.181 kg/m²) far exceeded the critical shear stress (0.003–0.007 kg/m²), indicating a high potential for bed erosion. Under minimum and average discharge, flow shear stress still exceeded the critical value, but sediment transport occurred with lower intensity and more stable flow conditions. Overall, the upstream flow is capable of mobilizing sediment significantly, so proper sediment management is needed to maintain the optimal function of the weir.